Functional Evaluation of Retinal Pigment Epithelium and Outer Retinal Atrophy by High-Density Targeted Microperimetry Testing - Zhichao Wu, BAppSc(Optom), PhD; Emily K. Glover, OD; Erin E. Gee, BAppSc(MedRad); Lauren A.B. Hodgson, MPH; Robyn H. Guymer, MBBS, PhD (Ophthalmology Science, 2024)
Purpose: Complete retinal pigment epithelium (RPE) and outer retinal atrophy (cRORA) on OCT imaging has recently been proposed to describe end-stage atrophy in age-related macular degeneration (AMD) by international consensus and expected to be associated with a dense scotoma, but such functional evidence is lacking. This study sought to examine the visual sensitivity defects associated with cRORA and to determine OCT features associated with deep defects. Design: Observational study. Participants: Sixty eyes from 53 participants, including 342 microperimetry tests over 171 study visits. Methods: Participants underwent targeted high-density threshold-based microperimetry testing of atrophic lesions (with at least incomplete RPE and outer retinal atrophy [iRORA]) with a 3.5° diameter grid. The maximum extent of signs of atrophy for all lesions was graded on OCT imaging. Main Outcome Measures: Number of deep visual sensitivity defects (threshold ≤ 10 decibels [dB]). Results: Presence of choroidal signal hypertransmission ≥ 500 μm, complete RPE loss ≥250 μm, and inner nuclear layer and outer plexiform layer subsidence, and hyporeflective wedge-shaped band (defined as nascent geographic atrophy [nGA]) ≥ 500 μm (P ≤ 0.020), but not RPE attenuation or disruption (P ≥ 0.192), were all independently associated with a significant increase in the number of deep visual sensitivity defects ≤ 10 dB. Only cRORA lesions with hypertransmission ≥ 500 μm or complete RPE loss ≥ 250 μm, or with both of these features (P < 0.001), but not lesions with only hypertransmission 250–499 μm (P = 0.303), had significantly more deep visual sensitivity defects ≤ 10 dB compared with iRORA lesions. Lesions with nGA ≥ 500 μm, irrespective of the presence of hypertransmission ≥ 500 μm and/or complete RPE loss ≥ 250 μm, also showed a higher number of deep visual sensitivity defects ≤ 10 dB compared with lesions without nGA ≥ 500 μm (P ≤ 0.011). Conclusions: Not all cRORA lesions show a difference in the number of deep visual sensitivity defects compared with iRORA. Instead, hypertransmission ≥ 500 μm, complete RPE loss ≥ 250 μm, and nGA ≥ 500 μm are all OCT features independently associated with deep visual sensitivity detects that could help inform the definition of end-stage atrophy on OCT imaging. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.